Studi komparatif kadar total flavonoid pada ekstrak n-heksana, etil asetat dan etanol daun mangkokan (Polyscias scutellaria) menggunakan spektrofotometer UV-Vis - Safrina Safrina; Yosie Haliza (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Mangkokan leaves (Polyscias scutellaria) are a plant with a million benefits from its extraordinary flavonoid content. Flavonoids are a group of compounds that are attracting attention because of their broad potential health benefits and applications in various fields, including nutrition, pharmaceuticals, and medicine.Objectives: Determine the total flavonoid content of mangkokan leaf extract using n-Hexane, ethyl acetate, and 70% ethanol as solvents.Methods: This is an experimental laboratory study by determining the total flavonoid content of mangkokan leaf extract (Polyscias scutellaria) based on differences in solvent polarity using UV-Vis spectrophotometry and comparing its flavonoid content with the ANOVA comparison test. The research was conducted at the Biology Biostatics Laboratory of the Faculty of Mathematics and Natural Sciences, Syiah Kuala University, the Biology Laboratory of the Aceh Ministry of Health Polytechnic, the Chemistry Laboratory of the Faculty of Mathematics and Natural Sciences, Syiah Kuala University, and the Pharmacy Laboratory of the Faculty of Mathematics and Natural Sciences, Syiah Kuala University, from December 1, 2023, to March 31, 2024. A sample of 1,5 kg of mangkokan leaves was obtained from Reuloh, Darul Imarah District, Aceh Besar Regency. The analysis carried out on the sample was phytochemical analysis and flavonoid content using a UV-Vis spectrophotometer instrument. The data obtained were analyzed statistically using the one-way ANOVA method.Results: The best results for determining the total flavonoid content of mangkokan leaves were given by the ethyl acetate extract solvent, namely 25,112 mgQE/g, followed by n-Hexane extract at 22,335 mgQE/g and 70% ethanol extract at 14,285 mgQE/g. The ANOVA test results showed that differences in solvents influenced the total flavonoid content of mangkokan leaf extract with a P value =0,00.Conclusion: The total flavonoid content of mangkokan leaf extract using an ethyl acetate solvent was higher compared to ethanol and n-Hexane solvents.KeywordsMangkokan leaves (Polyscias scutellaria), flavonoids, N-Hexane, ethyl acetate, Ethanol